Exploring reasons why South African dental therapists are leaving their profession: A theory-informed qualitative study. - Pumla Pamella Sodo; Yolanda Malele-Kolisa; Aneesa Moola; Veerasamy Yengopal; Simon Nemutandani; Sara Jewett (PLoS ONE, 2023)
Background Dental therapy is a category of mid-level oral health professional that was introduced to address inequities in oral health service provision in South Africa within a constrained human resource for health context. However, low numbers of registered dental therapists and attrition threaten this strategy. Aim This study explored reasons for this attrition, building on the Hertzberg Two-Factor Theory. Methods Through a qualitative exploratory study design, in-depth interviews were conducted with former dental therapists to explore their reasons for leaving the profession. They were recruited using snowball sampling. All interviews were audio recorded, transcribed verbatim, and coded in NVIVO12. A team of researchers applied thematic analysis to agree on themes and sub-themes, guided by Hertzberg's ideas of intrinsic and extrinsic factors. Findings All 14 former dental therapists interviewed expressed their passion for the profession, even though their motivations to join the profession varied. Many of their reasons for leaving aligned with extrinsic and intrinsic factors defined in Hertzberg's Two-Factor Theory. However, they also spoke about a desire for a professional identity that was recognized and respected within the oral health profession, health system, and communities. This is a novel study contribution. Conclusion Dental therapist attrition in South Africa is mainly caused by job dissatisfaction and motivation issues resulting from health system level factors. While the Hertzberg Two-Factor Theory helped identify extrinsic and intrinsic factors at an individual level, we used the Human Resources for Health System Development Analytical Framework to identify solutions for dental therapist production, deployment, and retention. Addressing these issues will enhance retention and accessibility to oral health services in the country.